The Effect of Estacoll and Reading Habit on the Eleventh Grade Students’ Writing Recount Text: A Lesson Learned from Private Schools - Ilahi, Rahma Kurnia; Amna, Fitra Afrida (JOLLT Journal of Languages and Language Teaching, 2025)
Writing is a crucial skill that students need to develop. In the process of writing, both writing techniques and reading habits play significant roles in shaping students' writing abilities. Therefore, selecting an appropriate teaching method is essential. The Estacoll technique can be employed as an alternative approach in teaching writing. This study aimed to examine the impact of the Estacoll technique on students' ability to write recount texts. The research utilized a quasi-experimental design, targeting eleventh-grade students in senior high schools. Two classes were randomly selected as the study sample. During the intervention, the experimental group was taught using the Estacoll technique, while the control group participated in small group discussions. The objective was to enhance the recount text writing skills of eleventh-grade students through the application of the Estacoll technique. This method serves as a strategy to improve students' knowledge and ability to produce well-structured recount texts. The study employed quasi-experimental methods, collecting data through writing tests and questionnaires. Statistical analysis was conducted using a t-test to evaluate the results. The data analysis aimed to demonstrate the effect of the Estacoll technique and reading habits on the recount text writing skills of eleventh-grade students. The findings revealed significant differences in students' writing abilities after the application of the Estacoll technique. In conclusion, this research highlights the potential of the Estacoll technique to offer students more opportunities to enhance their writing skills.